Improved mechanical and fatigue properties of graphene oxide/silica/SBR composites. Issue 65 (22nd August 2017) - Zhang, Songbo; Zheng, Long; Liu, Donghai; Xu, Zongchao; Zhang, Liqun; Liu, Li; Wen, Shipeng
Abstract : The fatigue lifetimes of the GO/SiO2 /SBR composites increased with the increase in GO content. Abstract : In this research, graphene oxide (GO) and silica reinforced styrene-butadiene rubber (SBR) composites were prepared by compounding GO/SBR masterbatch with silica. The influence of GO on the evolution of the filler network and crosslinking network of the composite during the fatigue process was investigated. Furthermore, the fatigue lifetimes of composites with different GO contents were obtained. The results showed that the GO sheets had a fine dispersion in the SBR matrix. The filler network constructed by GO and silica was improved after addition of the GO, resulting in the enhanced mechanical properties of the composites. During the fatigue process, the dispersion of GO and silica was enhanced, and the crosslinking density of the composites gradually decreased. S – N curves showed that the fatigue lifetime of the composites was improved after the addition of GO. Strain energy density can be used as a predictor of fatigue lifetime for the GO/silica/SBR composites.